Effect of type 2 diabetes mellitus on survival in metastatic pancreatic cancer - Sakin, Ayşegül; Sahin, Suleyman; Sakin, Abdullah; Atci, Muhammed; Geredeli, Çağlayan; Cihan, Şener (Journal of Surgery and Medicine, 2021)
Background/Aim: Many epidemiological studies describe a relationship between pancreatic cancer (PC) and Diabetes mellitus (DM). However, there are not enough studies investigating the effect of DM on survival of patients with metastatic PC. The purpose of this retrospective study was to investigate the effect of DM and its treatment on survival of patients with metastatic PC who received chemotherapy (CT) as first line treatment. Methods: Patients with metastatic PC who were followed up at the department of medical oncology between 2006 and 2018 were enrolled in this retrospective cohort study. Patients aged 18 years and over, who had metastatic disease at diagnosis and were treated with CT were analyzed. Patients with DM were stratified into two groups based on the history of medical treatments used for DM as follows: Oral antidiabetic (OAD) and OAD + insulin combination. Results: Following results were obtained after analyzing the medical records of 372 patients with metastatic PC, among which 125 (33.6%) had type II DM at the time diagnosis: The median age of the patients was 61 (range: 28-83) years. There were 136 (36.6%) female patients, and the median overall survival (OS) was 9.0 months in patients without DM, and 7.0 months (P=0.023) in those with DM. OS was 8.0 months in diabetic patients using OAD+insulin combination compared to 7.0 months in those receiving OAD (P=0.614) only. Multivariate analysis revealed that the presence of DM [Hazard ratio (HR), 1.43)], Eastern Cooperative Oncology Group Performance Status 3 (HR, 1.62), treatment with gemcitabine+Nab-paclitaxel (HR, 0.29) or folfirinox (HR, 0.46), and CA 19-9 level (HR, 1.01) were factors related to OS. Conclusion: In our study, we observed that the presence of DM adversely affected survival in metastatic PC patients who received CT as first line treatment; however, whether these patients used OAD or OAD+insulin combination did not affect survival.